Kekerasan terhadap Perempuan dan Anak dalam Perspektif Hukum di Indonesia - Putra, Refandi Alfian Eka (Verdict: Journal of Law Science, 2024)
Violence against women and children in Indonesia is a complex problem that requires serious attention and a multidimensional approach. This study aims to analyze the phenomenon of violence against women and children in Indonesia from a legal perspective. This study uses normative and legal methods that focus on assessing the existing legal framework, its implementation, and the challenges and opportunities in efforts to eliminate violence. The results indicate that Indonesia has a relatively comprehensive legal framework, including the Domestic Violence Law, the Child Protection Law, the Criminal Code and ratification of international conventions such as CEDAW. However, law enforcement still faces various obstacles, including a lack of understanding among law enforcement officers, limited resources, and socio-cultural barriers. This study identifies the multidimensional impacts of violence against women and children, including health, psychological, social, and economic aspects. Through this study, researchers recommend a series of strategic steps, including legal reform, increasing the capacity of law enforcement officers, expanding victim support services, and strengthening prevention efforts through education and public awareness campaigns. Better coordination between various stakeholders is also emphasized as the key to success in overcoming the problem of violence against women and children in Indonesia.